Avaliação do tempo de trânsito orocecal e da absorção de lactose e D- xilose em pacientes chagásicos constipados ou não e com e sem megacólon - Penhavel, Felix André Sanches (2014)
American Tripanosomiasis is one of the most prevalente tropical disease in Latin America. One third of brazilian territory is considered endemic for Chagas disease. Vectorial transmission is not complitely interrupted. In Central Brazil, specially Goiás State, digestive forms with megasyndormes have a high frequence. The involvement of small bowel has been discribed with functional disturbances. Patients with acquired megacolon may have normal bowel movements or long lasting constipation. Until now the influence of small bowel on the frequence of bowel movements is not clear. This prospective study addressed the small bowel motility measuring the orocecal transit time (OCTT) and the occurence of small bowel intestinal bacterial overgrowth (SIBO) by hydrogen breath test. 45 patients with positive serology for Chagas disease were divided into four groups: A – without megacolon and no constipation (17); B – with megacolon and no constipation (8); C – with megacolon and constipation (10) and D – without megacolon and constipation (10). Constipation was defined by at least 7 days without bowel movements. 15 healthy volunteers were taken as a control group (CG). Non hydrogen producers: 10/45 patients and 1/15 controls. The OCTT (medium time in minutes) was longer in patients than in controls: A=108.18, B=108.0, C=112.5, D=130.0 and CG=68.46. Patients together showed difference compared to controls (P=0.001). No difference was found among groups (P>0.05). The prevalence of SIBO was: 66.7% in constipated patients (C and D), 25% in non constipated patients (A and B) and 8.3% in controls. Significant statistical difference was found only comparing constipated patients and controls (P=0.017). The presence of megacolon did not show influence the frequence of SIBO (P=0.181). Lactose and D-xylose malabsorption was higher in controls. The number of patients with symptoms during the test was the same for chagasic and controls independently of the test result. Patients with Chagas disease have a prolonged OCTT and those with constipation showed a higher prevalence of SIBO and both factors are not related to megacolon. Chagasic patients showed a less frequency of lactose and D- xylose malabsorption.